HAK DESAIN INDUSTRI SAKLAR PUTAR (SWITCH GEAR) DITINJAU DARI UNDANG-UNDANG NOMOR 31 TAHUN 2000 TENTANG DESAIN INDUSTRI - Randy Prasetyo Utomo (CALYPTRA, 2014)
Industrial design is a creation about form, configuration or composition of line or colour, or line and colour, or both of them that form three dimension or two dimension which give aesthetic impression and can be realized in three dimension form or two dimension and can be used to make a product, goods, industrial commodity, or hand made product. Industrial design can only gives protection to the new design that a country can gives to the designer. And the person who have the right to the Industrial Design is the Designer or the other person who get that right from the Designer.